Didáctica intercultural de la educación física para el rescate y la práctica de los juegos ancestrales - Jara Arias, Juan Pablo (2018)
This research contributes to the Intercultural Didactics of Physical Education field, an area in which, before the study, there were no major contributions that develop the practical application of interculturality, as a transversal axis in the school context. The study was carried out in the Daniel Hermida educational unit in Cuenca, using a mixed approach, based on a previous analysis carried out to Physical Education teachers and students, which showed weaknesses in intercultural issues, lack of a teaching strategy and ignorance of ancestral games. Situation that motivated to elaborate a structured guide of interview directed to the settlers of the Santa Ana location, to rescue playful processes that can be applied of Physical Education. It was necessary to propose an intercultural guide, in which it is address empirically, three blocks of ancestral games, classified according to orientation, motor skills, precision, speed and intelligence, didactic instrument that was validated by experts, suggesting the application of the didactic guide in other school contexts. The total population of the educational institution is 359, therefore, a stratified intentional sample of 122 students was used. The total population of the educational institution is 359, therefore, a stratified intentional sample of 122 students was used. The guide was applied for 6 weeks, from September 3 to October 12, 2018, working on 2 periods per class, through a brief description and demonstration of the game, didactic resources, duration, evaluation, qualities and physical abilities that each game brings. It was developed in open spaces, with a domestic animals interaction, prefabricated implements and from the natural environment. Finally, during the investigation it is concluded that teachers and students ignore the application of interculturality as a transversal axis, on the other hand, the ancestral games allow the exchange of products, strengthening of axiological processes, reciprocal reciprocal behavior framed in the exchange of motor experiences, communication horizontal, interaction and harmonious coexistence.